Examining The Efficacy of Music Therapy Incorporating Classical Compositions and Traditional Folk Melodies (Azerbaijani, Iranian) to Alleviate The Intensity of PTSD Symptoms - Yousefi, Asraf (Institut Seni Indonesia Padangpanjang, 2024)
This study investigates the effectiveness of music therapy using both local (Azerbaijani, Iranian) and classical melodies in reducing the severity of PTSD symptoms in individuals with post-traumatic stress. A total of 60 participants, selected from public and private clinics in Tabriz between June 2015 and 2016, were divided into three groups: classical music therapy, native/local melody therapy, and a control group. PTSD symptom severity was measured at three intervals: pre-test, post-test, and a 3-month follow-up, using mixed variance analysis. A PTSD diagnostic scale questionnaire was administered by experts. The results showed no statistically significant difference between the local and classical music therapy groups (p=0.954). However, both the local and classical music therapy groups experienced a significant reduction in PTSD symptoms compared to the control group (p<0.01), indicating that music therapy, regardless of the type of melody, is effective in alleviating PTSD symptoms. These findings highlight the potential of music therapy as a non-invasive treatment for PTSD. Future research could explore long-term effects and cultural variations in music therapy